Journey of a book: Bartholomew the Englishman and the Properties of Things Bartholomew the Englishman and the Properties of Things - Keen, Elizabeth (ANU Press, 2007)
De proprietatibus rerum, 'On the properties of things', has long been referred to by scholars as a medieval encyclopedia, but evidence suggests that it has been many things to many people. The sheer number of extant manuscript copies and printed editions, along with translations, adaptations, and mentions in poems and sermons, testify to its continuous significance for Europeans of all estates and different walks of life, from the thirteenth to the seventeenth centuries. While first compiled soon after the time of St Francis by a humble continental friar to meet the needs of his expanding religious brotherhood, by 1600 English men of letters had claimed Bartholomew as a noble compatriot and national treasure. What was it about the work that propelled it through a progression of medieval cultures and into an exalted position in the world of English letters? This reception history traces evidence for the journey of 'Properties' over four centuries of social, political and religious change.